Incidence, aetiology and neurodisability associated with severe microcephaly: a national surveillance study. Issue 3 (9th December 2022) - Knowles, Rachel L; Solebo, Ameenat Lola; Sampaio, Mariana Autran; Brown, Charlotte Rebecca; Sargent, Jenefer; Oluonye, Ngozi; Rahi, Jugnoo
Abstract : Objective: To determine the incidence, causes and neurodevelopmental impact of severe microcephaly (head circumference <–3SD) up to age 2 years. Design: Binational active paediatric surveillance study undertaken in 2017–2018 to identify and characterise new diagnoses of severe microcephaly. Setting: UK and Ireland. Participants: Infants aged under 12 months at diagnosis. Interventions: Observational study. Main outcome measures: Incidence, aetiology and neurodevelopmental outcomes at age 2 years. Results: Fifty-nine infants met the case definition, of whom 30 (51%) were girls; 24 (41%) were born preterm (<37 weeks' gestation); and 34 (58%) were of 'white' ethnicity. Eight (14%) children died before 12 months of age. Incidence of severe microcephaly was 5.5 per 100 000 infants (95% CI 4.0 to 7.3). Higher relative risk (RR) was associated with preterm birth (RR 7.7, 95% CI 3.8 to 15.1) and British Asian ethnicity (RR 3.6, 95% CI 1.6 to 7.8). Microcephaly was mainly due to genetic causes (59%), brain ischaemia/hypoxia (10%) and congenital infection (8%), and 19% remained undetermined. Each child was referred on average to eight specialists, and 75% had abnormal brain imaging. By 2 years of age, 55 children experienced neurodevelopmental abnormalities, including feeding problems (68%), motor delay (66%), visual impairment (37%), hearing loss (24%) and epilepsy (41%). Conclusions: Although severe microcephaly is uncommon, it is associated with high mortality, complex multimorbidity and neurodisability, thus representing a significant ongoing burden for families and healthcare services. Potentially preventable causes include preterm birth, hypoxic/ischaemic brain injury and congenital infections. Clinical guidelines are essential to standardise aetiological investigation and optimise multidisciplinary management.